POTRET KEBIJAKAN DAN IMPLEMENTASI ANGGARAN RESPONSIF GENDER DI PEMERINTAH PROVINSI NTB: Perspektif Komunikasi Organisasi - Kadri Kadri (Pusat Studi Gender dan Anak Universitas Islam Negeri (UIN) Mataram, 2020)
By using an organizational communication perspective, this research focuses on uncovering the policies, planning, implementation and evaluation of the Gender Responsive Budget and women's empowerment in Nusa Tenggara Barat (NTB) Province. The results of this qualitative research show that although the NTB Provincial Government has the political will of a gender responsive budget and women's empowerment by setting relevant regulations and missions, but in planning and implementing the budget it has not optimally accommodated the spirit of gender responsive and women's empowerment. Organizational communication of the NTB Provincial Government is more internal, while external communication with stakeholders who have competence in the field of women's empowerment seems minimal so there are still women's problems in NTB that have escaped the attention of the provincial government.